Organic Chemistry of DNA Functionalization; Chromophores as DNA Base Substitutes versus DNA Base/2′-Modifications - Schmucker, Wolfgang; Wagenknecht, Hans-Achim (Synlett, 2012)
Nucleic acids are suitable scaffolds for the precise arrangement of different kinds of artificial functionalities inside or along the double helix. In this account, we summarize our synthetic efforts over the last ten years to modify DNA chemically with organic chromophores, fluorescent probes, and metal-ion ligands. We used three different approaches: (i) replacement of DNA bases (substitutes/surrogates), (ii) modifications of DNA bases (mainly 2′-deoxyuridine), and (iii) sugar modifications at the 2′-position. The first two types of modifications were achieved mainly by the DNA building block approach, whereas the latter type is based on postsynthetic methodologies. The different synthetic concepts are described and the influence of representative modifications on the melting temperature is compared.
Keywords: chromophore; oligonucleotide; building block; fluorescence; energy transfer